MERANCANG PENDIDIKAN EKONOMI DAN BISNIS ISLAM PADA DESA CINANGNENG, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Anwar, Miftakhul; Nurhasan, Abdul Khodir; Tajriya, Hania (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2023)
Islamic business economics education needs to be introduced and taught to the public, so that the public understands Islam not only as a ritual of worship, but also as an economy and business. With a good understanding of Islamic economics and business, the community can contribute to sustainable economic development and strengthen social welfare in accordance with the economic goals of the Republic of Indonesia contained in the preamble to the constitution. The community service activity which was carried out by being located in Cinangneng Village, Tenjolaya District, Bogor Regency, aimed to provide an understanding of Islamic economic and business education. In the end, people understand Islam and Islamic economics and business.